Ginseng Holds Promise Against Obesity - Rabia Rehan; Mahrukh Kamran; Ayesha Abdul Haq; Sahar Mubeen; Maria Khan; Hira (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Objectives: To determine the effects of ginseng on obese albino rats. Methods: This study was intended to correlate the role of ginseng in reducing body weight, liver weight and size as well as fatty accumulation in hepatocytes of male albino rats weighing between 110g to 140g. This experiment was designed to study the morbid anatomy of an animal model. It was conducted in Animal house of Dow University of Health Sciences. Fifty male Albino Wistar rats were divided into 5 groups. Group1 (Gp 1) was on normal balanced diet (control), Group 2 (Gp 2) was on high fat diet (HFD), Group 3 (Gp 3) on HFD plus ginsenoside 100 mg/kg body wt., Group 4 (Gp 4) on HFD plus ginsenoside 200mg/kg body wt., and Group 5 (Gp 5) on HFD plus 400mg/kg body. Results: Weight was increased to 146 g (Gp1) and 236g (Gp 2). Group 3 reduced weight from 236g to 211g. Group 4 to 192g and Group 5 to 171g. Liver weight is also increased by HFD from 4.7g (Gp1) to 9.3 g (Gp 2). Liver weight decreased from 9.3g to 7.2g (Gp 3), 7.6 g (Gp 4) and 5.3 g (Gp 5). Due to deposition of fat in liver, cells enlarged and number of hepatocytes decreased per unit area of reticule. Number of hepatocytes in group 1 was 78.5, in group 2 WAS 38.3, in group 3 was 47.4, in group 4 was 53.8 andin group 5 was 67.7. Random blood sugar (RBS) was altered to 74.3 mg/dl in Gp1, 148 mg/dl in Gp2, 91 mg/dl in Gp3, 92 mg/dl in Gp4 and 69 mg/dl in Gp5. Conclusion: The results of this study revealed that HFD is a major cause of obesity and it should be prevented by introducing ginseng as an anti-obesity in our life. This study concluded that ginseng root extract proves to be more potent as anti-obesity, anti-hyperlipidemic, anti-hyperglycemic and anti-oxidant.